Synthesis of Fullerenes from a Nonaromatic Chloroform through a Newly Developed Ultrahigh-Temperature Flash Vacuum Pyrolysis Apparatus - Hong-Gang Zhang; Ya-Qi Zhuo; Xiao-Min Zhang; Leng Zhang; Piao-Yang Xu; Han-Rui Tian; Shui-Chao Lin; Qianyan Zhang; Su-Yuan Xie; Lan-Sun Zheng (Nanomaterials, 2021)
The flash vacuum pyrolysis (FVP) technique is useful for preparing curved polycyclic aromatic compounds (PAHs) and caged nanocarbon molecules, such as the well-known corannulene and fullerene C60. However, the operating temperature of the traditional FVP apparatus is limited to ~1250 °C, which is not sufficient to overcome the high energy barriers of some reactions. Herein, we report an ultrahigh-temperature FVP (UT-FVP) apparatus with a controllable operating temperature of up to 2500 °C to synthesize fullerene C60 from a nonaromatic single carbon reactant, i.e., chloroform, at 1350 °C or above. Fullerene C60 cannot be obtained from CHCl3 using the traditional FVP apparatus because of the limitation of the reaction temperature. The significant improvements in the UT-FVP apparatus, compared to the traditional FVP apparatus, were the replacement of the quartz tube with a graphite tube and the direct heating of the graphite tube by impedance heating instead of indirect heating of the quartz tube using an electric furnace. Because of the higher temperature range, UT-FVP can not only synthesize fullerene C60 from single carbon nonaromatic reactants but sublimate some high-molecular-weight compounds to synthesize larger curved PAHs in the future.